Glial Cells and Brain Diseases: Inflammasomes as Relevant Pathological Entities - Mata-Martínez, Esperanza; Díaz-Muñoz, Mauricio; Vázquez-Cuevas, Francisco G. (Frontiers in Cellular Neuroscience, 2022)
Inflammation mediated by the innate immune system is a physiopathological response to diverse detrimental circumstances such as microbe infections or tissular damage. The molecular events that underlie this response involve the assembly of multiprotein complexes known as inflammasomes. These assemblages are essentially formed by a stressor-sensing protein, an adapter protein and a non-apoptotic caspase (1 or 11). The coordinated aggregation of these components mediates the processing and release of pro-inflammatory interleukins (IL-β and IL-18) and cellular death by pyroptosis induction. The inflammatory response is essential for the defense of the organism; for example, it triggers tissue repair and the destruction of pathogen microbe infections. However, when inflammation is activated chronically, it promotes diverse pathologies in the lung, liver, brain and other organs. The nervous system is one of the main tissues where the inflammatory process has been characterized, and its implications in health and disease are starting to be understood. Thus, the regulation of inflammasomes in specific cellular types of the central nervous system needs to be thoroughly understood to innovate treatments for diverse pathologies. In this review, the presence and participation of inflammasomes in pathological conditions in different types of glial cells will be discussed.